MEMBANGUN RASA PERCAYA DIRI MELALUI PUBLIC SPEAKING DALAM KEGIATAN CERAMAH AGAMA DI MAN 2 KOTA BENGKULU - Dwi Mutiara, Ilvia Anggun; Mindani; Rio Putra, Deko; Arini Julia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to build students’ self-confidence through public speaking activities conducted in religious speech programs at MAN 2 Kota Bengkulu. Self-confidence is an essential psychological aspect that supports students’ communication skills; however, many students still experience anxiety, fear, and low confidence when speaking in public. This research explores the implementation of public speaking through religious speech activities, identifies supporting and inhibiting factors, and analyzes their contribution to students’ self-confidence development. The study employed a qualitative case study approach. Data were collected through participatory observation, in-depth interviews, and documentation involving guidance and counseling teachers, religious supervisors, subject teachers, and students. Data analysis followed the interactive model of Miles and Huberman, including data collection, data reduction, data display, and conclusion drawing. The findings indicate that religious speech activities conducted regularly after the Dhuha prayer function as an effective experiential learning medium for public speaking practice. Students gradually demonstrated increased confidence, improved speaking fluency, better voice control, and more effective nonverbal communication. Teacher guidance, a supportive religious school environment, and structured scheduling emerged as key supporting factors, while internal anxiety and limited peer support were identified as inhibiting factors. Overall, the study concludes that building self-confidence through public speaking in religious speech activities positively enhances students’ communication skills and personal development.